Comparative analysis of human and mouse 3′ Igh regulatory regions identifies distinctive structural features - Sepulveda, Manuel A.; Garrett, Francine E.; Price-Whelan, Alexa; Birshtein, Barbara K. (Molecular immunology, 2005)
Immunoglobulin heavy chain ( Igh) locus rearrangements are controlled in part by an ∼30 kb complex 3′ regulatory region located 3′ of Cα: this region contains several enhancers. We report here the comparison of the genomic sequences of the 3′ regulatory region and further downstream sequences from mouse, rat, human and chimpanzee. Only short segments of homology were detected in the 3′ regulatory region, and these were located in the vicinity of the known 3′ enhancers. The nearest highly conserved segment is the nearest non- Igh gene, hole, which is located ∼62 kb downstream of mouse Cα. Analysis of murine 3′ Igh sequences by single nucleotide polymorphism (SNP) and restriction fragment length polymorphism (RFLP) detected a transition region (high to low SNP or RFLP density) ∼120 kb downstream of mouse Cα. Although there is only limited sequence identity between rodent and primate 3′ Igh regulatory regions, all of these regulatory regions contain a palindrome and locally repetitive elements. Locally repetitive elements in primates comprise blocks of “switch-like” sequences that differ from the families of inverted and tandem repeats that are present in rodents. We propose that together with enhancers, these “conserved” structural features are essential for the activity of the 3′ Igh regulatory region in vivo.